2019
DOI: 10.2105/ajph.2019.305159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Food-Labeling and Advertising Law Banning Competitive Food and Beverages in Chilean Public Schools, 2014–2016

Abstract: Objectives. To evaluate the impact of a national law banning sales of competitive food and beverages (CF&B) in schools on the availability of CF&B sold at school kiosks. Methods. This study was uncontrolled before and after study. We evaluated public schools in Santiago de Chile (n = 21; 78% response rate) in 2014 and 2016 (6 months after the law came into force). Trained personnel collected data on calories, total sugars, saturated fat, and sodium from food labels. The outcome was the percentage of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
1
28
1
1
Order By: Relevance
“…In addition, along with the warning-label component, the Chilean law includes marketing and school sales restrictions, which likely contributed to the larger effect found here. A recent evaluation found that schools reduced the percent of products that were high-in from 90.4% before implementation to 15.0% after implementation [70], which may have influenced children's preferences and the subsequent household purchase made by their parents. Indeed, a separate qualitative study found that schools were a key promotor of behavioral change relating to the labeling component of the law: children learned about the regulation at school and then encouraged their mothers to purchase nonlabeled foods and beverages for them [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, along with the warning-label component, the Chilean law includes marketing and school sales restrictions, which likely contributed to the larger effect found here. A recent evaluation found that schools reduced the percent of products that were high-in from 90.4% before implementation to 15.0% after implementation [70], which may have influenced children's preferences and the subsequent household purchase made by their parents. Indeed, a separate qualitative study found that schools were a key promotor of behavioral change relating to the labeling component of the law: children learned about the regulation at school and then encouraged their mothers to purchase nonlabeled foods and beverages for them [71].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the food environment was regulated, banning the sales of these foods in schools and the marketing of products in the media for children under 14 years of age. [142][143][144] While the overarching impact of these changes is still under analysis, recent studies have shown that people understand well the labeling and that after implementation they improve food healthiness classification and decrease the purchases of "high-in" products of some food categories such as sweet-sugared beverages and breakfast cereals. Similarly, food-ad exposure on television decreased among preschoolers and adolescents and the exposure to unhealthy food products at the school also decreased substantially.…”
Section: Population-based Effortsmentioning
confidence: 99%
“…The wear-out effects of repetition of marketing exposure could also be studied by exploring non-linear relationships between marketing exposure and consumption [53], which was not accounted for in the present study. Further developing understanding of the relationship between SSB marketing and consumption could help policymakers develop multicomponent strategies to address SSB consumption, such as that currently being modelled in Chile [60]. For example, if SSB taxes lead to unintended changes to marketing, they could be introduced alongside greater SSB marketing restrictions.…”
Section: Implications Of Findings and Future Researchmentioning
confidence: 99%